Analisis Persepsi Wisatawan Terhadap Daya Tarik Dan Strategi Promosi Destinasi Wisata Urban di Surabaya: Studi Kasus Rustic Market, Kalimas Cruise, dan Surabaya North Quay - Krissanty Aulia Dewi; Fiolita Eunike; Pattira Eldayanara; Mohammad Insan Romadhan (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to analyze tourist perceptions of attraction and promotional strategies in three urban tourism destinations in Surabaya: Rustic Market, Kalimas Cruise, and Surabaya North Quay. These destinations represent diverse forms of urban tourism combining aesthetics, history, and maritime themes. The study adopts a qualitative descriptive approach with data collection techniques including field observation, in-depth interviews with tourists and managers, as well as digital documentation through social media platforms and online reviews. The findings reveal that each destination has its unique appeal, but digital promotion strategies remain underdeveloped. Rustic Market excels in visual aesthetics but lacks official digital presence; Kalimas Cruise offers historical river tourism but limited online visibility; while Surabaya North Quay is active only during cruise arrivals and lacks consistent digital engagement. A structured digital promotion strategy, cross-destination campaigns, and collaboration with communities and local MSMEs are recommended. This study highlights the importance of synergy among government bodies, tourism operators, and tourists to create sustainable tourism promotion.